Pola Pemahaman Hadis Partisipan Kegiatan One Day One Hadis dalam Whatsapp - Jendri Jendri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The purpose of this study is to find out and explain the concept of understanding of hadith in one day one hadith in whatsap which includes the understanding of hadith material. The emergence of One Day One Hadith (ODOH) itself only exists in contemporary times now, because it is the effect of the rapid development of technology and information and communication that is increasingly sophisticated. Especially in the media of Whatsaap there is a textualist (closed), hermeneutic, and contextualist understanding of the Prophet's hadith, so that the message or message conveyed can be disseminated and practiced. Whatsaap is one of the many social media that can communicate anything to humans in various regions, especially information about the hadith. This study is based on the assumption that the dynamics of hadith studies in the global era and social media dias are at least the impact of the emergence of traditions contained in whatsaap. The birth of one day one hadith effort itself is at least not departing from an empty space. Socially the system adopted in one day one hadith (ODOH) has given its own color for Indonesia, especially Muslims. With the step of spreading the hadith one day one hadith, the point is to make it easier to find and understand the hadith. Therefore, further analysis and study of the concept of understanding in one day one hadith in whatsap in the current era. This research uses a type of library research (lebrary research) that is research by collecting data and studying books or library literature related to this discussion. Then in data management using descriptive and analysis methods (content analysis). Whereas in drawing conclusions using the deductive method in which the collected data is processed systematically and selectively, then conclusions are drawn which are the results of the study. The results of this study indicate that the hadith lives up to the end of time, in understanding it it is necessary to use various concepts of understanding including textual, hermeneutic, and contextual, so that in understanding the hadith is not confusing when dealing with problems in contemporary times now.